Differences of Composition Operators Followed by Differentiation between Weighted Banach Spaces of Holomorphic Functions. (12th November 2013) - Chen, Cui; Chen, Ren-Yu; Zhou, Ze-Hua
Abstract : We characterize the boundedness and compactness of differences of the composition operators followed by differentiation between weighted Banach spaces of holomorphic functions in the unit disk. As their corollaries, some related results on the differences of composition operators acting from weighted Banach spaces to weighted Bloch type spaces are also obtained.